The mediating effects of buyer-supplier relationship on relationship of trust and commitment, and organization performance of agriculture based SMEs in Kelantan - Nor Zawani, Mamat @ Ibrahim (2014)
Previous studies had justified that buyer-supplier relationship has a positive relationship with organization performance of SMEs. Plus, the positive relationship between trust and buyer-supplier relationship of SMEs also has been indicated in a past studies. However, not many researches were done to study the commitment effect on buyer-supplier relationship, and the mediating effect of buyer-supplier relationship with trust, commitment, and organization performance of SMEs. In addition, there are few researches done in primary agriculture based SMEs that are focusing on micro enterprise is and this situation needs to be changed since this sector has contributed 7.3% to the Malaysia Gross Domestic Product (GDP). This study fills up the gap by identifying the relationship of trust, commitment, buyer-supplier relationship and organization performance of primary agriculture based SME's concentrating on micro enterprise. Plus, this study has presented the hypothesis regarding this relationship. This study concentrates on SMEs' primary agriculture of micro enterprise type located in Kelantan, whereby Kelantan is the third ranking state with the most number SMEs‟ involvement in Malaysia with a total about 37, 823 SMEs. The questionnaires were distributed to 120 respondents and 100 questionnaires were returned back. However, two questionnaires had to be rejected because there were not fully completed. So, the total number of samples in this study is 98. A list of the respondents was retrieved from Jabatan Pertanian Negeri Kelantan, complete with an email address and contact number. The finding shows that there is a positive relationship between trust and commitment on buyer-supplier relationship, and there is a positive relationship between buyer-supplier relationship and organization performance of primary agriculture based SMEs in micro enterprise type. However, buyer-supplier relationship is a partial mediator of the relationship between trust and commitment to organization performance. The recommendation of the organization and future research were also discussed.